THE LINKAGE OF STOCK TRADING DECISIONS, EI TRAITS, FINANCIAL LITERACY, AND RISK TOLERANCE ON GENERATION Z - Bertha Silvia Sutejo (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
This study applied the dual process theory to explain the relationship between two systems in decision-making. The first system is associated with emotional intelligence (EI) traits. The second system is associated with financial literacy. Therefore, this study examines the two systems' effect on stock trading decisions by using a quantitative approach with non-probability and purposive sampling methods. The questionnaire was distributed to 350 Generation Z investors in Indonesia via Google Forms from July 2024 to September 2024. The study applied the SEM model with Amos statistical software and the Sobel Test using the Sobel calculator. As the results, this study indicate that the stock trading decision-making for Generation Z is influenced by System 2. While System 1 has no effect on their stock trading decision-making. Emotional intelligence (EI) traits do not affect stock trading decision-making, while financial literacy does. Financial tolerance also fully mediates the relationship between emotional intelligence (EI) traits and stock trading decision-making. Risk tolerance mediates some of the relationship between financial literacy and stock trading decision-making.